Modeling and Simulation of Closed Loop Controlled Parallel Cascaded Buck Boost Converter Inverter Based Solar System - T. Sundar; S. Sankar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This Work deals with design, modeling and simulation of parallel cascaded buck boost converter inverter based closed loop controlled solar system. Two buck boost converters are cascaded in parallel to reduce the ripple in DC output. The DC from the solar cell is stepped up using boost converter. The output of the boost converter is converted to 50Hz AC using single phase full bridge inverter. The simulation results of open loop and closed loop systems are compared. This paper has presented a simulink model for closed loop controlled solar system.  Parallel cascaded buck boost converter is proposed for solar system.